2010
DOI: 10.1088/0957-4484/21/50/505102
|View full text |Cite
|
Sign up to set email alerts
|

Development of a nanoparticulate formulation of diminazene to treat African trypanosomiasis

Abstract: There is a real need to develop new therapeutic strategies for African trypanosomiasis infections. In our study, we developed a new drug delivery system of diminazene (DMZ), a trypanocidal drug registered for veterinary use. This drug candidate presents a limited efficacy, a poor affinity for brain tissue and instability. The development of colloidal formulations based on a porous cationic nanoparticle with an oily core ((70)DGNP(+)), has potentially two advantages: stabilization of the drug and potential targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 21 publications
3
17
0
Order By: Relevance
“…It would, therefore, be of interest to conduct similar studies to establish the protective or curative effects of diminazene aceturate compared to the appropriate control groups. Recent studies have also shown that colloidal nanoparticle formulations of diminazene exhibited greater activity against T. brucei brucei in vitro and had increased delivery to the brain in mice (Kroubi et al 2010(Kroubi et al , 2011.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It would, therefore, be of interest to conduct similar studies to establish the protective or curative effects of diminazene aceturate compared to the appropriate control groups. Recent studies have also shown that colloidal nanoparticle formulations of diminazene exhibited greater activity against T. brucei brucei in vitro and had increased delivery to the brain in mice (Kroubi et al 2010(Kroubi et al , 2011.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have also shown that colloidal nanoparticle formulations of diminazene exhibited greater activity against T. brucei brucei in vitro and had increased delivery to the brain in mice (Kroubi et al. , ).…”
Section: Resultsmentioning
confidence: 99%
“…The porous cationic nanoparticles used stepped forward the potential focused on of trypanosomes. Evaluation of medical parameters after nanoparticle treatment revealed a partial reduction of allergic conditions [93].…”
Section: Nanotechnology Applications In Veterinary Therapeuticsmentioning
confidence: 98%
“…Several other reports show the usefulness of nanoparticles in disease diagnosis (Na et al, 2009;Jackson et al, 2011;Schlacter et al, 2011;Huang et al, 2012). Nanotechnology is currently employed in the treatment of African animal trypanosomosis (Kroubi et al, 2010). It enabled the development of a new drug delivery system against diaminazene (DMZ) a trypanocidal drug registered for veterinary use.…”
Section: Nanotechnology Applications In Veterinary Diagnostics and Thmentioning
confidence: 99%